Reporting Big News, Missing the Big Picture? Stock Market Performance in the Media - Antonio Ciccone; Felix Rusche (CESifo GmbH, 2025)
Between 2017 and 2024, the main national stock market indices rose in the US and the five largest European economies. However, the average daily performance of all six indices turns from positive to negative when weighted by daily media coverage. A case in point is the average daily performance of Germany's DAX index on days it was reported on the country's most-watched nightly news. While the DAX increased by more than 4 index points per day over the period, the index dropped by more than 10 points on days it was reported – news was bad news. On days the DAX wasn't covered on the nightly news, the index rose by around 10 points – no news was good news. About half of the worse daily performance when the DAX was covered is accounted for by a greater focus on negative news. The other half stems from a novel big news bias: a greater focus on large index changes, whether positive or negative, combined with a negative skew in the daily performance of the index. We show that the big news bias extends to other national stock market indices.
Keywords: L82; G10; 330; media bias; financial markets.